Numerical simulation of pressure transients caused by high-speed train passage through a railway station. (15th October 2020) - Liang, Xi-Feng; Chen, Guang; Li, Xiao-Bai; Zhou, Dan
Abstract: In this study, an experimental and computational study of the pressure transients of a high-speed train passing through a station is presented. The experiments were performed using 1/20th scale train models with a head car and an end car on a moving model rig with a speed of 300 km/h. The pressure transients were measured using kulite pressure sensors on the car body surface and the platform screen roof and doors. Computationally, an overset grid and an IDDES k-w turbulence model were adopted to simulate the pressure transients inside a railway station. A numerical simulation with different platform screen doors heights was conducted. The obtained results showed that the CFD simulation results were consistent with the reduced-scale test results. The peak pressure coefficient distribution for the station roof bottom surface, platform screen door surface, and details of the flow field structure is also presented in this article. Moreover, the application of the CEN Standard to practical engineering issues concerning the pressure load and time interval is discussed. Highlights: A 1/20 moving model experiment is established to model movement of the high-speed train relative to the ground. IDDES k-w turbulence model combined with overset grid is used to model the moving of train and detailed flow field. The CFD results were validated with moving model experiment. The application of the CEN Standard to practical engineering issues is discussed.